Need Analysis of Student Worksheets Based on Case Method to Develop Problem-Solving Skills - Fitriatien, Sri Rahmawati; Mustaji, Mustaji; Fajar Arianto (JTP - Jurnal Teknologi Pendidikan, 2025)
Currently, the pharmaceutical mathematics class has implemented the case method. However, many students still experience difficulties in organizing problem-solving in solving problems offered in the form of case studies. 70% of students have not focused on the problems offered during learning activities due to the lack of guidelines for solving the problems discussed. Therefore, it is necessary to conduct a needs analysis of student worksheets based on the case method to develop problem-solving skills. This study employed a quantitative descriptive method, involving lecturers teaching the pharmaceutical mathematics course and 68 students of the pharmacy study program at Universitas PGRI Adi Buana Surabaya as the research samples. Data collection techniques used were interviews and questionnaires with percentage formulas. The results of the interviews indicate that lecturers need to create student worksheets based on the case method to direct the learning process. Moreover, the questionnaire results showed that students really need case method-based student worksheets as a guide in solving problems in case studies.  This study is an initial study for the development of student worksheets based on the case-based pharmaceutical mathematics course to develop students' problem-solving skills.